Assessment of dopperfluxometric indices of maternal-fetal structures in pregnant ewes - Santos, Victor José Correia [UNESP]; Rodriguez, Mariana Garcia Kako [UNESP]; Silva, Priscila Del Aguila Da [UNESP]; Mariano, Renata Sitta Gomes [UNESP]; Taira, Augusto Ryonosuke [UNESP]; Padilha-nakaghi, Luciana Cristina [UNESP]; Uscategui, Ricardo Andres Ramirez; Feliciano, Marcus Antonio Rossi [UNESP]; Oliveira, Maria Emilia Franco [UNESP]; Moraes, Paola Castro [UNESP]; Vicente, Wilter Ricardo Russiano [UNESP] (Colégio Brasileiro de Reprodução Animal, 2021)
The aim of this study was to evaluate the blood flow of the uterine artery, fetal aorta and umbilical artery in the physiological pregnancy of sheep by means of pulsed Doppler throughout the gestational period. Thirty Santa Inês ewes weighing between 45.4±4.3 kg and aged 2 to 5 years were selected. The evaluations were carried out weekly from the 3rd to the 21st gestational week. Peak systolic velocity (PSV), end diastolic velocity (EDV) and resistance index (RI) were obtained. Analysis of variance was performed, and the minimum significant comparison of means was obtained by the BH test with adjusted P<0.05. The results were expressed as mean ± standard error. For the fetal aorta, there was an increase in the EDV values and a decrease in the PSV and RI throughout pregnancy. For the uterine artery, PSV and EDV did not present significant variation, whereas the RI showed a reduction in the last week. Increased EDV values were found for the umbilical artery throughout pregnancy. For the PSV there was no significant difference, as the RI was reduced at the end of pregnancy. The results obtained are expected to contribute to a more complete understanding of the hemodynamic changes resulting from pregnancy.
Keywords: ultrasonography; Doppler; sheep; pregnancy